2012
DOI: 10.1073/pnas.1217296110
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted and transgenic urate oxidase alter urate and dopaminergic neurodegeneration

Abstract: Urate is the end product of purine metabolism in humans, owing to the evolutionary disruption of the gene encoding urate oxidase (UOx). Elevated urate can cause gout and urolithiasis and is associated with cardiovascular and other diseases. However, urate also possesses antioxidant and neuroprotective properties. Recent convergence of epidemiological and clinical data has identified urate as a predictor of both reduced risk and favorable progression of Parkinson's disease (PD). In rodents, functional UOx catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 112 publications
(129 citation statements)
references
References 42 publications
6
123
0
Order By: Relevance
“…In vivo, genetic manipulation of urate oxidase and resulting increased concentrations of urate in the CNS led to improved phenotype and histopathologic findings in PD mouse models [35,49]. These data substantiate earlier findings in PC12 cells, in which urate blocked cell death and oxidative damage induced by either dopamine [50] or 6-hydroxydopamine [51].…”
Section: Urate Is Neuroprotective In Several Preclinical Models Of Nesupporting
confidence: 81%
See 1 more Smart Citation
“…In vivo, genetic manipulation of urate oxidase and resulting increased concentrations of urate in the CNS led to improved phenotype and histopathologic findings in PD mouse models [35,49]. These data substantiate earlier findings in PC12 cells, in which urate blocked cell death and oxidative damage induced by either dopamine [50] or 6-hydroxydopamine [51].…”
Section: Urate Is Neuroprotective In Several Preclinical Models Of Nesupporting
confidence: 81%
“…Neuroprotective [35] Neuroprotective in SCI, brain ischemia/stroke, MS [38][39][40][41] Clinical trials SURE-PD (phase II trial) [10] URICO-ICTUS (phase IIb/III trial in stroke) [42,43] PD = Parkinson's disease; ALS = amyotrophic lateral sclerosis; AD = Alzheimer's disease; HD = Huntington's disease; MSA = multiple system atrophy; MCI = mild cognitive impairment; SCI = spinal cord injury; MS = multiple sclerosis …”
Section: In Vivomentioning
confidence: 99%
“…12) In the present study, we found that XO mRNA levels were significantly lower in SHRSP (Table 4). Reductions in urate content due to a decrease in XO mRNA level may also be partly involved in the high levels of oxidative stress observed in the SHRSP cerebrum.…”
Section: Discussionsupporting
confidence: 55%
“…Urate, the end‐product of human purine metabolism, is an endogenous antioxidant10, 11 and proposed neuroprotectant12, 13, 14, 15 and its levels may be increased by edaravone treatment 6, 16. High urate levels correlate with improved survival in ALS epidemiologic studies17, 18, 19, 20, 21, 22, 23 and with favorable outcomes in other neurodegenerative diseases, most notably Parkinson's disease (PD) 24, 25, 26.…”
Section: Introductionmentioning
confidence: 99%
“…High urate levels correlate with improved survival in ALS epidemiologic studies17, 18, 19, 20, 21, 22, 23 and with favorable outcomes in other neurodegenerative diseases, most notably Parkinson's disease (PD) 24, 25, 26. Further, urate is neuroprotective in several models of neurodegeneration 12, 27, 28, 29, 30, 31, 32…”
Section: Introductionmentioning
confidence: 99%